2016
DOI: 10.1186/s12978-016-0138-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of maternal health care services and their determinants in Karnataka State, India

Abstract: BackgroundKarnataka State continues to have the highest rates of maternal mortality in south India at 144/100,000 live births, but lower than the national estimates of 190–220/100,000 live births. Various barriers exist to timely and appropriate utilization of services during pregnancy, childbirth and postpartum. This study aimed to describe the patterns and determinants of routine and emergency maternal health care utilization in rural Karnataka State, India.MethodsThis study was conducted in Karnataka in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 14 publications
8
74
0
Order By: Relevance
“…Space constrained labour-rooms and obstructions caused by the use of curtain in attending to multiple women simultaneously have been cited as potential reasons that providers do not use curtains for privacy [11,5254]. Facility cleanliness in terms of clean linen in the wards, with frequent cleaning of the wards and toilets was a significant determinant of women’s overall satisfaction of services, which often are irregular and disorganised [5559]. Management of complications as necessary, in addition to good health of the mother and child, are the most desirable aspect of care expressed by the women in this study as well as others,, as these elements affect their health and survival [27,37,41].…”
Section: Discussionmentioning
confidence: 99%
“…Space constrained labour-rooms and obstructions caused by the use of curtain in attending to multiple women simultaneously have been cited as potential reasons that providers do not use curtains for privacy [11,5254]. Facility cleanliness in terms of clean linen in the wards, with frequent cleaning of the wards and toilets was a significant determinant of women’s overall satisfaction of services, which often are irregular and disorganised [5559]. Management of complications as necessary, in addition to good health of the mother and child, are the most desirable aspect of care expressed by the women in this study as well as others,, as these elements affect their health and survival [27,37,41].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][20][21][22][23][24][25][26] A study done in Rohilkhand region by Srivastava, A et al in 2014 also identified a number of demographic and socio-economic factors such as education, religion etc. to be the major causes of poor utilization of primary health care services.…”
Section: Acknowledgementmentioning
confidence: 99%
“…The finding was supported by other studies and the association of parity with the ANC utilization of maternal health care services was found to be statistically significant. [2][3]21,17 The reason could be mothers with lesser number of child (esp. with the first child) are more cautious and concerned about pregnancy and thus likely to undertook healthcare visits.…”
Section: Acknowledgementmentioning
confidence: 99%
“…But women in most countries dropout before completing the full component of maternity continuum of care [3].In many countries, there is a significant dropout among women who had ANC visitbefore getting other subsequent maternal health care services [5,6]. This dropout or failure to access skilled birth attendants and postnatal care results for compromised health and wellbeing of both the mother and newborn [7].…”
Section: Introductionmentioning
confidence: 99%